Corporate Reputation Management in Times of Crisis: The Contribution of Brand Image and CSR in Unilever Indonesia - Yulianti, Wulan; Setyaningtyas, Emilya; Liryana, Khansa Arshy; Wijaya, Tirta Nata Adi (Communicare : Journal of Communication Studies, 2025)
The Israel–Palestine conflict has prompted Indonesia, the world’s second-largest Muslim nation, to boycott products perceived as supporting Israel. Unilever Indonesia was among the companies affected, raising concerns about reputational damage. In response, the company sought to strengthen its Corporate Social Responsibility (CSR) initiatives. This study examines the influence of brand image and CSR on Unilever Indonesia’s corporate reputation during the crisis. A quantitative approach was employed using surveys with purposive non- probability sampling. Findings based on the R2 value indicate that brand image and CSR together account for 87.6% of the variance in corporate reputation. Brand image demonstrated a significant effect (t = 7.404), while CSR also showed a significant effect (t = 4.666). These results confirm that both brand image and CSR positively and significantly affect corporate reputation. The study highlights that in times of crisis, a strong brand image and well-managed CSR initiatives play a crucial role in maintaining and enhancing corporate reputation.